Nursing students' views on the COVID-19 pandemic and their percieved stress levels - Aslan, Hakime; Pekince, Hatice (Wiley, 2021)
Purpose This study was conducted to evaluate nursing students' views on the COVID-19 pandemic and their perceived stress levels. Design and Methods A cross-sectional design was used to carry out this study. The research was conducted between April and May 2020 with 662 nursing students. Data were collected by an information form developed for the study and the Perceived Stress Scale (PSS). Findings The average score on the PSS was 31.69 +/- 6.91, indicating that the students had a moderate level of stress. Significant differences in PSS score were found in terms of age and sex (P < .001 andP < .001, respectively). Practice Implications Results of this study indicated that age, sex, and some variables related to the pandemic process affect perceived stress levels of nursing students.
Keywords: coronavirus disease; COVID-19; nursing students; perceived stress; perceived stress scale